Total Fenolik dan Aktivitas Antioksidan Seduhan Kulit Batang Soni (Dillenia serrata Thunb) - Melati Sukma; Nurlansi; Nasrudin (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2022)
Total Phenol and Antioxidant Activity Of Soni Skin Steeping Extract (Dillenia serrata Thunb). This study aims to find out phenolic levels and antioxidant activity of Soni Stem Skin Steeping (Dillenia serrata Thunb). The total levels of phenolics contained in soni stem skin steeping are determined by the reagent folin cioelteau, sodium carbonate with gallic acid as a comparison, while its antioxidant activity with the DPPH method. The skin of the soni stem used is the skin of the dried soni stem that has been smoothed. As much as 20 g of soni stem bark powder brewed with hot water dispenser, brewing is done 3 times with the first brewing volume of 80 mL, secondly 60 mL, last 20 mL using solvents sourced from the dispenser. Powder extract from steeping the skin of the soni stem is then collected so that the volume of the soni stem steeping sample is obtained as much as 150 mL. Extract results in steeping of soni stem skin, determined by total phenolic level and antioxidant activity. The total phenolic level of stem skin is 17.06 AGE/gram. Soni bark steeping extract has very weak antioxidant activity with IC50 value of 2,377,5925 ± 0.2031 ppm.